Seeking To Be Self Sufficient - Sunday Star, Mohd Peter Davis (2008)
As the world food crisis threatens billions with hunger and starvation an international call has been made for the Food and Agriculture Organisation (FAO) emergency conference in Rome (June 3 to June 5) to completely restructure world agriculture and double world food production.